RESIPROSITAS DALAM BUDAYA NGAMBEK AHIAN PADA MASYARAKAT DESA AUR DURI KECAMATAN RAMBANG NIRU KABUPATEN MUARA ENIM - Septi Saputri (Jurnal Media Sosiologi (JMS), 2021)
This study examines "Reciprocity in Ngambek Ahian Culture in the People of Aur Duri Village, Rambang Niru District, Muara Enim Regency". The purpose of this study is to determine the reciprocity that exists in the ngambek ahian culture in Aur Duri Village. The method used in this study is qualitative descriptive method. The data collection techniques used were participant observation, in-depth interviews and documentation. This research uses the theory of Reciprocity from Mauss and Sahlins and the theory of Reciprocity Value from Molm, et al. The results of this study show that reciprocity in ngambek ahian culture includes reciprocal relationships between family, neighbors and friends. This reciprocal relationship is inseparable from the process of implementing the ngambek ahian culture which starts from the stage before implementation, the stage of the day of implementation and the stage after implementation. Then this type of reciprocity in the culture of ngambek ahian is of general and comparable type. This common and comparable reciprocity is found in the reciprocal relationships between family, neighbors and friends. Furthermore, the reciprocity value found in the ngambek ahian culture is an instrumental and symbolic value.